KUALITAS PROSES DAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN BERBASIS PROYEK PADA SISWA KELAS SDN 2 RAMPA KOTABARU - Abi Sara; Faisal Batennie (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2015)
The problem of the study is low quality of process and learning result in mathematics of class V student at SDN 2 Rampa in Kotabaru. The study aims at examining (a) the improvement of process quality and learning result in mathematics on nets geometry throught project-based learning of class V student at SDN 2 Rampa in Kotabaru?.(b) Is there an increase in the quality of mathematics learning about geometry nets project-based learning of class V student at SDN 2 Rampa in Kotabaru?. The study employed qualitative approach with a classroom action research with in cycles which consisted of the planning, the implementation, observation, and reflection. The subjects of the study were teachers and 25 students of class V student at SDN 2 Rampa in Kotabaru. Data were collected d through observation,test,questionnaire, and dokumentation. Data were analyzed using qualitative data analysis. The result of the study revealed that the project-based learning process can improve the quality of learning process in mathematics on nets geometry of class V student at SDN 2 Rampa in Kotabaru viewed from the teaching activity and student’ learning in cycle I and II as well the improvement of the quality of learning result in mathematics on net geometry throught project-based learning of class V students at SDN 2 Rampa in Kotabaru viewed from the improvement of the result of pre-test in cycle I cycle II. Therefore, the conclusion of the study is there is improvement of process quality and learning result in mathematics through project-based learning of class V at SDN 2 Rampa in Kotabaru. Keywords: Quality Learning Process And Results, Math Through, Project Based Learning